The Asymmetric Impact of Exchange Rates on Indonesia's CPO Export Value - Utami Lestari, Sri; Alamsyah, Zulkifli; Rahmah, Karina (JALOW | Journal of Agribusiness and Local Wisdom, 2023)
This study examines the asymmetric effect of the rupiah exchange rate on Indonesia's Crude Palm Oil (CPO) exports during the period 2006 to 2023. Utilizing the Nonlinear Autoregressive Distributed Lag (NARDL) approach, this study captures the short-term and long-term asymmetric relationship between exchange rate fluctuations and export values. Earlier research typically use linear models on aggregate data, thus possibly ignoring sector-specific dynamics. This study, on the other hand, focuses on the unique characteristics of CPO exports, which reveal different responses to rupiah appreciation and depreciation. The results of the analysis indicate a significant asymmetric effect in the long run, where rupiah depreciation increases the competitiveness of CPO exports, while appreciation tends to decrease it. However, no significant asymmetric impact was found in the short run. The NARDL analysis reveals that depreciation in the exchange rate exerts a more significant influence on export performance compared to appreciation., thus supporting the need for adaptive policies to maintain export stability in the CPO sector.